Linguopoetic Features of Translating Conceptual Linguistic Units (Based on the Materials of Poetic Discourse) - Fedoskina, G. (M.S. Narikbayev KAZGUU University School of Liberal Arts. Astana, 2025)
The purpose of this qualitative study is to analyse the linguopoetic features of poetic discourse and the applied strategies and techniques in the process of translating poems. This descriptive-comparative analysis is based on four poems in Russian and English, where its translations are compared and described, and two universally applicable classifications of strategies and techniques by scholars Lefevere (1975) and Molina and Albir (2002). To fulfil these objectives, this study is prevailed by content analysis, which contributes to a detailed examination of each poetic sample, namely the works “Russia”, “Eugene Onegin” (the first three poems of the first chapter), “The Raven”, and “Birches”. Semantic, stylistic and cultural analyses are applied to reveal the linguopoetic features of the poems. In the course of analysing these works, the study highlights certain linguistic elements found in Russian and English poetry, as well as the specifics of its translation. Translation of poetic texts into a foreign language, including English or Russian remains controversial to this day. Thus, nowadays it is possible to determine a huge number of interpretations of the same work. Results of this qualitative study demonstrate the diversity of linguopoetic features, strategies and techniques in translating poetic works and illustrate the importance of preserving not only the semantic content of such types of texts, but also the aesthetic content. Drawing on the identified conclusions, this research recommends that translators of poetry should apply an extended number of translation tools, not excluding a diverse selection of poetic poems, while considering possible differences in linguistic culture. This research paper expands the required knowledge and contributes to the field of poetry translation by vividly illustrating all the nuances that arise in the process of this type of translation
Keywords: poetic discourse, poetry translation, poem, linguopoetic features, strategies, techniques, semantics, stylistics, culture